City-Tour: 25 Jahre Mauerfall. Neues von der historischen Stadtbrache. - Schüller, Nicola; Klein, Jochen (Routledge, 2015)
During the 25 years that have passed since the Wall fell, the space left by the Wall has changed, not only in its physical form, but also in how it is perceived. One example is how this history-charged site is dealt with in architectural projects. Starting in the early 1990s, the city government was focused on continuously reconnecting the two City halves by reconstcucting the prewar blocks, thus erasing all traces of its history. However, in recent years some projects were developed that managed to integrate traces of the Wall. The photographs document a section of the inner-city part of the Wall between the districts of Berlin-Mitte and Berlin Kreuzberg in the time-period between 1988-1989 and 2014. They show changes and stagnation in the brownfield left by the Wall, allowing the viewer to draw inferences on the politics and culture of building construction in Berlin over the last 25 years.
Keywords: Stadtentwicklung; Stadtgestaltung; Brachfläche; Mauer; Bebauung; Rekonstruktion; Stadtbrache; Kritische Rekonstruktion